Effect of esketamine on postoperative quality of recovery in patients undergoing arthroscopic rotator cuff repair: protocol for a prospective, randomized, double-blind study - Qirong Sun; Jiao Luo; Shijia Zhang; Leng Zhou (Trials)
Abstract Background The utilization of shoulder arthroscopic surgery has progressively increased as a prevalent surgical approach for the treatment and repair of rotator cuff injury in clinical practice. However, early postoperative pain and neurological dysfunction remain significant factors that impact patients’ postoperative recovery. Esketamine, an NMDA receptor antagonist, effectively reduces opioid consumption, attenuates postoperative inflammatory reactivity, and has also demonstrated neuroprotective effects. The aim of this study is to evaluate the quality of early recovery after anesthesia maintenance with esketamine in patients undergoing arthroscopic rotator cuff repair. Methods This is a single-center, randomized controlled trial. A total of 234 patients undergoing arthroscopic rotator cuff repair will be enrolled and randomized at a 1:1:1 ratio to receive general anesthesia with different doses of esketamine or saline solution. The primary outcome is the quality of early recovery scores based on the QoR-15 scale on postoperative day 1. Secondary outcomes include the quality of early recovery scores based on the QoR-15 scale on postoperative day 3, remifentanil consumption, use of vasoactive drugs, cerebral desaturation events, rescue analgesia during the post-anesthesia care unit stay, NRS pain scores on postoperative days 1 and 2, delirium within 3 days after surgery, and adverse events. Discussion A randomized controlled trial design will be used in this study to assess the quality of early recovery scores in patients undergoing arthroscopic rotator cuff repair. Our objective is to investigate the potential of esketamine in mitigating the adverse effects associated with intraoperative controlled hypotension and assessing its impact on intraoperative cerebral oxygen saturation and postoperative delirium. Although this study is conducted at a single center, and there is limited research on the long-term effects of perioperative esketamine on patients, it still offers valuable insights for future studies. Trial registration This study has been approved by the Ethics Committee at West China Hospital, Sichuan University (approval no. 2023–2282). Trial registration number ChiCTR2400080589. Registered on 2024.02.01.